RAB39B: A novel biomarker for acute myeloid leukemia identified via multi-omics and functional validation - Chen Shuo; Li Mengxing; Wang Jishi (Open Medicine)
The objective of this research was to investigate the involvement of RAB39B in acute myeloid leukemia (AML) using bioinformatics analysis and in vitro experiments for validation.